THE ALTERATION OF ORGANIC MATTER IN RESPONSE TO IONISING IRRADIATION: CHEMICAL TRENDS AND IMPLICATIONS FOR EXTRATERRESTRIAL SAMPLE ANALYSIS - Court R.W.; Sephton M.A.; Parnell J.; Gilmour I. (My University, 2006)
Ionising radiation is an energy source capable of generating and altering complex organic matter. A full understanding of the radiolytic formation and evolution of organic matter is essential to appreciate the budget of organic chemicals that exist in cometary and interstellar ices, carbonaceous meteorites, and to understand the results of analyses of irradiated extraterrestrial organic matter, such as that in cometary nuclei. The effects of ionising radiation on a set of 10 naturally occurring, terrestrial organic assemblages have been revealed by pyrolysis-gas chromatography-mass spectrometry (Py-GC-MS), carbon isotopic analysis, and stepped combustion-isotope ratio mass spectrometry (SC-IRMS). Progressive radiolytic alteration of biogenic complex-hydrocarbon mixtures induces a decrease in the average size and extent of alkylation of polyaromatic hydrocarbons (PAH) and an increase in the abundance of oxygen-containing compounds, as indicated by Py-GC-MS, and an enrichment in 13C. These changes are attributed to reactions with free radicals, produced by ionising radiation. In contrast, the progressive radiolytic alteration of bitumens proposed to have derived from the radiolytic polymerisation of methane into an organic solid produces, upon pyrolysis, PAH of increasing average size and degree of alkylation. This, the opposite of the trend observed in the irradiated complex-hydrocarbons mixtures, cannot be explained in terms of the radiolytic alteration of a pre-existing array of complex organic molecules. Instead, it suggests the gradual construction of PAH from smaller molecules, supporting the hypothesis of a methane origin. Radiolytic alteration is also associated with a previously unrecognised increase in the mean combustion temperature of organic matter. This leads to predictions regarding the combustion characteristics of the irradiated organic matter present on cometary nuclei. A full understanding of the relationship between the combustion characteristics of organic polymers, radiation dose and the atomic H/C ratio should lead to the better design and implementation of in situ extraterrestrial sample analysis hardware and aid the interpretation of data from such missions. This study establishes predictable organic chemical responses of organic matter, upon exposure to ionising radiation. Our results support proposals that extraterrestrial PAH may be formed by the cosmic irradiation of simple hydrocarbons in interstellar ices. Our data may also be relevant to analogous material formed in other hydrocarbon-rich environments, such as the surface and atmosphere of Titan and other icy bodies, such as comets, and to the results of in situ analyses of extraterrestrial organic matter. ? 2005 Elsevier Inc. All rights reserved.
Keywords: EXTRATERRESTRIAL MATTER; ORGANIC GEOCHEMISTRY; ORGANIC MATTER; RADIATION EXPOSURE